Analysis of Paradigm Shift Toward the Transformation of Nahdlatul Ulama’s Political Orientation - Abadi, Mansurni; Arraki, Rajih; Shukyzhanova, Aiym (Balai Penelitian dan Pengembangan Agama Semarang, 2023)
This article discusses the process of paradigm shift of Nahdlatul Ulama (NU)’s national politics orientation. Considering Thomas S. Kuhn's paradigm shift concept, particularly the revolutionary stages, there was a separation of the national political transformation period in NU. A paradigm shift which opens awareness in understanding the science does only happens in established objectivity. The product of ijtihad, due to the deposition of knowledge, always has natural subjectivity with what they believe as the truth. Thus, innovative movements in finding alternative linear formulations that can always form dialogue with the times must always be carried out. Through literary work, this article illustrates that demarcation boundaries of the occurrence of NU's national political shift characterized by the pre-normal phase, normal phase, anomaly-crisis phase, and new-normal phase. Utilizing Kuhn’s perspective as tool of analysis, this study finds out that there are a few stages of paradigm shift experienced by NU. NU's struggles marked the pre-normal phase as an embryo before finally becoming an organization. The birth and development of NU marked the intermediate phase as a socio-political-religious organization on the track of the struggle. The anomaly-crisis phase occurred when NU metamorphosed into a political party, involved in interests, and strayed from its goals. The new-normal phase was marked by NU's return to Khittah in 1926, which meant returning to a social-religious-based organization. NU has returned to the struggle to fill and maintain independence through national politics in this phase.